Pengembangan E-Modul Berbasis Problem Based Learning (PBL) Terintegrasi TPACK Pada Materi Usaha Dan Energi - Tasya Salsabila; Pintor Simamora (Universitas Muhammadiyah Magelang, 2026)
This research aimed to develop a valid, practical, and effective physics e-module based on Problem Based Learning (PBL) integrated with TPACK (Technological Pedagogical Content Knowledge) on work and energy material for grade XI high school students. The research employed a 4-D development model (Define, Design, Develop, Disseminate) with a total of 45 participants consisting of 10 students in the small group trial and 35 students in the large group trial. The e-module was developed using Canva application and distributed through the Heyzine Flipbook platform. Research results demonstrated that the e-module received very valid rating from content experts with a score of 96.6% and valid rating from media experts with a score of 77.8%. Practicality testing revealed very practical results from physics teachers (96.6%), small group trial (99%), and large group trial (99.42%). Effectiveness testing using normalized N-Gain showed a learning outcome improvement of 0.68 in the medium category, with a change in mean score from 52.86 on the pre-test to 85 on the post-test. The physics e-module based on PBL integrated with TPACK was declared very valid, very practical, and effective as a teaching material for high school physics. It proved capable of significantly improving students' conceptual understanding and learning outcomes.